1995
DOI: 10.1227/00006123-199508000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Substrates for Astrocytoma Invasion

Abstract: A better understanding of the influences of specific extracellular substrates, including proteins, glycosaminoglycans, and parenchymal cells, on the invasive behavior of glioma cells would potentially lead to novel forms of treatment aimed at confining the tumor. A monolayer, microliter scale assay was used to investigate how different substrates influenced glioma migration. Basal or unspecific movement (range, 10-260 microns/d) was determined by observing a panel of seven established human glioma cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…The distribution of tenascin-C at the invasive edge of malignant gliomas, and even surrounding solitary invading cells, strongly suggests a role for this protein as a regulator of glioma cell migration (Treasurywala and Berens, 1998). However, in contrast to the response to other matrix proteins, glioma cells migrating on tenascin-C do not follow a characteristic dose-dependent pattern since tenascin-C can act as both a permissive (at low densities) and a nonpermissive (at high densities) motility substrate (Treasurywala and Berens, 1998;Giese et al, 1996b). Thus, the gastrin-induced decrease in human glioblastoma cell motility we reported previously (DeHauwer et al, 1998) could be mediated, at least in part, through a dramatic gastrin-induced increase in tenascin-C expression leading to non permissive densities and consequently to a decrease in cell motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of tenascin-C at the invasive edge of malignant gliomas, and even surrounding solitary invading cells, strongly suggests a role for this protein as a regulator of glioma cell migration (Treasurywala and Berens, 1998). However, in contrast to the response to other matrix proteins, glioma cells migrating on tenascin-C do not follow a characteristic dose-dependent pattern since tenascin-C can act as both a permissive (at low densities) and a nonpermissive (at high densities) motility substrate (Treasurywala and Berens, 1998;Giese et al, 1996b). Thus, the gastrin-induced decrease in human glioblastoma cell motility we reported previously (DeHauwer et al, 1998) could be mediated, at least in part, through a dramatic gastrin-induced increase in tenascin-C expression leading to non permissive densities and consequently to a decrease in cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to laminin (Giese et al, 1994), myelin (Giese et al, 1996a) and ®bronectin (Enam et al, 1998), tumor astrocytes also use the N-CAM neural adhesion molecule (Sasaki et al, 1998), tenascin-C (Giese et al, 1996b) and a number of glycoproteins including a central segment of the NG2 proteoglycan (Burg et al, 1997) and the brain-enriched hyaluronan binding (BEHAB)/brevican gene product (Zhang et al, 1998) in their migration. Of all these ECM components tenascin-C is expressed only by tumor astrocytes from malignant gliomas, and not by normal astrocytes (Gladson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Glioma-derived ECM has been previously shown to enhance the motility behavior of these cells. 10,20,33 To compare the Fn14 gene expression level among different cell lines, Fn14 mRNA levels were normalized to the level found in G112 cells, where Fn14 gene expression was initially characterized. 20 Northern blot data indicated that the ϳ1.2-kb human Fn14 transcript was detected in four glioma cell lines under standard culture conditions ( Figure 1A).…”
Section: Induction Of Fn14 Mrna and Protein Expression In Glioma Cellmentioning
confidence: 99%
“…Giese et al 39 observed a five times higher migration rate of glioma cells on TN-C-monolayers than on collagen, fibronectin, or vitronectin layers using seven human glioma cell lines in a microliter scale assay. In vitro, endothelial cells attach to TN-C substrates and are able to elongate and extend as necessary for endothelial migration; in contrast, there was no spread on substrates, including fibronectin, collagen, vitronectin, or laminin.…”
Section: Tn-c In Brain Tumorsmentioning
confidence: 99%